Nursing outcomes guideline in major post-floods communities in Indonesia - Agianto, Agianto; Setiawan, Herry; Nasri, Novi Mustahdiati; Yunara, Yulia; Karunia, Muhammad; Aminullah, Muhammad Fasya; Noo, Rezka Aulyan; Yulianti, Dwi Wanda (Intelektual Pustaka Media Utama, 2025)
Health problems resulting from flooding have a very significant role in the sustainability of people's lives. Major floods hit South Kalimantan, Indonesia in 2021. The impact of the flooding will cause nursing problems in the community. There has been no research on nursing outcomes for communities affected by floods, although research has been conducted on identifying nursing diagnoses for post-flood communities. The aim of the research is to develop nursing outcomes for nursing diagnosis in post-flood communities in Indonesia. Descriptive analytics with a cross-sectional approach. The research sample was 140 people with a consecutive sampling technique using a questionnaire with 207 assessment items on nursing outcomes for nursing diagnoses that emerged in post-flood communities. Univariate analysis was used. The 14 nursing diagnoses that emerged in flood-affected communities, there are 33 nursing outcomes labels with 91 outcome indicators. Nursing diagnoses and nursing outcomes that have been obtained can be made into a guidebook for nursing care in post-flood communities. The quality of nursing services can be improved when a disaster occurs to reduce disability, complications and even death during and after a flood disaster.